Pendidikan Karakter pada Anak Usia Dasar dalam Pembelajaran Daring di Era Digital - Husain, Alma Pratiwi (Lembaga Rumah Indonesia, 2021)
The development of the digital technology era makes educators have to provide extra character planting in children. Character education as a character / moral shaper of a child. The COVID-19 pandemic has changed the pattern of human life, one of which is in the field of education which has turned into online learning. This study aims to describe the character education of elementary-aged children in online learning in the digital era. The research method used is library (Library Research). The results of the study show that to instill character education in elementary age children in the online learning process in the digital era, it is necessary to optimize all aspects of both educators, students, parents, and the learning curriculum. Thematic-integrative in the 2013 curriculum can be used as an alternative character education. During the COVID-19 pandemic, character cultivation in children can still be taught, especially on the value of spiritual, responsible and independent character.